Influence of Measurement Error on a New-Voltage-less Distance Protection Method - Li, Linjie; Biller, Martin; Jäger, Johann (IEEE PESS Power and Energy Student Summit, 2018)
On the one hand, closed ring operation of medium-voltage distribution networks leads to benefits such as voltage balancing and reduction of transportation losses and thus increases the networks capacity to integrate DERs. On the other hand, some significant problems for conventional distance protection arise. A new distance protection based on negative-sequence currents has been developed in order to determine the distance from the fault location to the relays at the substation for unbalanced faults. The impact of measurement errors from current transformers (CTs) and voltage transformers (VTs) on the accuracy of the new method is a question that remains. Thus, in this paper, an appropriate network model of an excerpt of a distribution grid is investigated. Steady-state fault calculation of unbalanced faults under several system states is executed using MATLAB. The impact of measurement errors from CTs and VTs on the determination of distance is considered. The results show that the distance results of the new method are by far more accurate than for the conventional distance protection method in most of the cases, even under the impact of measurement errors caused by CTs and VT
Keywords: closed ring; distance protection; measurement errors